Family Influences on Heart Failure Self-care and Outcomes - Dunbar, Sandra B. (2008)
Many patient education guidelines for teaching heart failure patients recommend inclusion of the family; however, family-focused interventions to promote self-care in heart failure are few. This article reviews the state of the science regarding family influences on heart failure self-care and outcomes. The literature and current studies suggest that family functioning, family support, problem solving, communication, self-efficacy, and caregiver burden are important areas to target for future research. In addition, heart failure patients without family and those who live alone and are socially isolated are highly vulnerable for poor self-care and should receive focused attention. Specific research questions based on existing science and gaps that need to be filled to support clinical practice are posed.